Implementation of Smart Meeting Room Videowall All in One Using Project Management Framework Methodology at PT. Pupuk Sriwidjaja Palembang - Muhammad Azhari; Muhammad Febrian; Tata Sutabri (Yayasan Cita Cendekiawan Al Khwarizmi, 2023)
Smart meeting room is a